Segunda cita de Colibri thalassinus para la Argentina - Bertelli, Sara; Morfulis, Marcelo; Aragón, Roxana; Malizia, Lucio R.; Lomáscolo, Teresita (El Hornero, 1997)
Este artículo no cuenta con un resumen.